คุณภาพการให้บริการของพนักงานขายที่ส่งผลต่อการตัดสินใจเลือกใช้บริการของลูกค้าศูนย์การค้าสุพรีม ในช่วงสถานการณ์ COVID-19 - สังข์โสม , นันทวัน; กุศลาไสยานนท์, เชฐธิดา; ปิณฑะแพทย์ , จุฑารัตน์ (วารสารพัฒนาธุรกิจและอุตสาหกรรม, 2024)
The objectives of this research were to 1) study customers’ behavior in using services, 2) study customers’ opinion regarding service quality, 3) study customers’ decision for choosing services in shopping center, 4) compare customers’ behavior of using different services leading to choose shopping center, and 5) study the service quality of sales staff affecting the decision in choosing the service of customers in shopping center. The sample in this study were 400 customers using the service in Supreme Shopping Center, using a questionnaire as a tool to collect data. The statistics for analyzing the collected data were frequency, percentage, mean, standard deviation, and Multiple Regression Analysis. As results found that 1) most of customer’s intended to use services in restaurant, search information channel via internet, receive better service than general department stores, use services for price value, get service for 6-7 time per month, recommend persons at work to use services, value in service, and keep continue using the restaurant service; 2) the opinion level regarding service quality of sales staff in the overall were at high level; 3) the decision level in choosing services of customer in shopping center in the overall were at high level; 4) the behavior comparison of using services classified by different ate customer’s intention for using service in restaurant, search information channel, better service than general department stores, using service for creating value, frequency of using service, recommending the others to use the service, and continuous using the restaurant, have decision in choosing service in difference; and 5) The service quality of sales staff in aspect of concreteness of service, reliability or trustworthiness, and confidence affecting the decision to choose the services with statistical significance at the .05 level.